Hormonal contraception and risk for cognitive impairment or Alzheimer's disease and related dementias in young women: a scoping review of the evidence - Gregory, Sarah; Booi, Laura; Jenkins, Natalie; Bridgeman, Katie; Muniz-Terrera, Graciela; Farina, Francesca R. (Frontiers in Global Women's Health, 2023)
Introduction Women are significantly more likely to develop Alzheimer's disease and related dementias (ADRD) than men. Suggestions to explain the sex differences in dementia incidence have included the influence of sex hormones with little attention paid to date as to the effect of hormonal contraception on brain health. The aim of this scoping review is to evaluate the current evidence base for associations between hormonal contraceptive use by women and non-binary people in early adulthood and brain health outcomes. Methods A literature search was conducted using EMBASE, Medline and Google Scholar, using the keywords “hormonal contraception” OR “contraception” OR “contraceptive” AND “Alzheimer*” OR “Brain Health” OR “Dementia”. Results Eleven papers were identified for inclusion in the narrative synthesis. Studies recruited participants from the UK, USA, China, South Korea and Indonesia. Studies included data from women who were post-menopausal with retrospective data collection, with only one study contemporaneously collecting data from participants during the period of hormonal contraceptive use. Studies reported associations between hormonal contraceptive use and a lower risk of ADRD, particularly Alzheimer's disease (AD), better cognition and larger grey matter volume. Some studies reported stronger associations with longer duration of hormonal contraceptive use, however, results were inconsistent. Four studies reported no significant associations between hormonal contraceptive use and measures of brain health, including brain age on MRI scans and risk of AD diagnosis. Discussion Further research is needed on young adults taking hormonal contraceptives, on different types of hormonal contraceptives (other than oral) and to explore intersections between sex, gender, race and ethnicity. Systematic Review Registration https://doi.org/10.17605/OSF.IO/MVX63, identifier: OSF.io: 10.17605/OSF.IO/MVX63